Investigation of Natural Circulation Flow Under Steady-State Conditions Using a Rectangular Loop - Roswandi, Iwan; Dimas, Dimas; Gunawan, Hyundianto Arif; Budiman, Arif Adtyas; Amelia, Almira Citra; Sanda, Sanda; Tjahjono, Hendro; Juarsa, Mulya (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2024)
Passive safety systems have garnered significant attention, particularly in situations where active systems fail. The comprehension of natural circulation phenomena plays a vital role in the advancement of passive cooling systems in nuclear power plants. The objective of this study is to examine the flow patterns under steady state conditions and assess the Grashof number. The experimental approach involved maintaining temperature differences of 60°C, 70°C, 80°C, and 90°C for a duration of 3 hours, with 3 replications. Alterations in temperature have an impact on the physical properties of water, such as density, viscosity, and specific heat. The calculations indicate that the minimum Grashof number occurs at 60°C (2.49×1012), while the maximum is observed at 90°C (9.42×1012), with an R2 value of 0.96533. Turbulent flow patterns were observed during each temperature fluctuation, which aligns with previous research on the Ress value of Grm/NG.